Regulation of private placements in the EU - Elomaa, Laura (fi=Turun yliopisto|en=University of Turku|, 2017)
The subject of this legal dogmatic and comparative thesis is private placements and their regulation in the European Union. A private placement is an alternative funding method, an exemption regime provided in Prospectus Directive, which allows, under certain conditions, companies to issue an offering without an obligation to publish a prospectus. Despite the private placement regime, the EU market of private placements is fragmented. This study aims to find an answer whether the EU should regulate the instrument more comprehensive to create a more vivid private placement market to the Europe. In Europe, the bank financing plays a significant role in financial markets, and therefore alternative funding methods, such as private placements are also in the interest of regulators. Anyway, private placements are often criticised to ensure only poor protection to investors, which is of a particular interest in this study. This thesis examines EU regulation covering private placements, describes shortly the regulation and market practices of the top three European private placement markets as well as explains the main features of the U.S. private placement market as a purpose to identify some best practices. Lack of investor protection is concern connected to private placements both in the EU and in the U.S., and therefore a comparison between these two continentals are done with regard to investor protection and private placements. Finally, the thesis concludes with a discussion on pros and cons of harmonizing private placements at the EU level.